Development of the method of multi-criteria evaluation of hierarchical systems - Sova, Oleg; Stanovskyi, Oleksandr; Hurskyi, Taras; Olshanskyi, Valentyn; Volkov, Oleksandr; Shostak, Serhii; Bezuhlyi, Vitalii; Tikhonov, Hryhorii; Chaikovska, Olena; Razarionov, Leonid (Eastern-European Journal of Enterprise Technologies, 2025)
Multicriteria evaluation offers undeniable advantages over single-criterion assessment methods. The object of the study is hierarchical systems. The subject of the study is the process of multicriteria evaluation of the state of hierarchical systems. A method for multicriteria evaluation of hierarchical systems is proposed. The originality of the method lies in the application of additional advanced procedures that allow for the following: – verification of input data and refinement of inter-element connections within the hierarchical system using an enhanced penguin swarm algorithm. This minimizes the risk of errors resulting from incorrect data input in the assessment of the operational military (force) grouping; – description of external and internal factors affecting the hierarchical system subject to multicriteria evaluation through the use of fuzzy cognitive models; – adaptation to the type of hierarchical system via multilevel adjustment of the system of indicators and evaluation criteria; – reduction of uncertainty through the use of interval-valued Pythagorean fuzzy sets, thereby improving the reliability of multicriteria assessment of hierarchical system states; – identification of the most vulnerable elements within the hierarchical system using a fault tree analysis; – adaptation of the membership function type depending on the system’s available computational resources, which ensures compatibility with existing computational capacities. An example of the method’s application is demonstrated through the multicriteria evaluation of an operational military (force) grouping. The proposed method provides an average improvement of 35% in accuracy and efficiency, while ensuring a high convergence rate of results at the level of 93.17%